Application of Ultrasonic Waves on Decaffeination Process of Gayo Aceh Arabica Coffee - Jannah, Jumrotul; Yuniati, Yuyun; Sucahyo, Bambang Sigit; Handarini, Kejora (Program Studi Teknologi Pangan Fakultas Pertanian UNSOED, 2025)
Gayo Aceh Arabica coffee is famous for its quality and unique taste. However, caffeine-sensitive consumers often stay away from this coffee because excessive caffeine intake can have a detrimental effect on health. Therefore, the decaffeination process is important in producing low-caffeine coffee without reducing its distinctive taste and aroma. The research focused on assessing the influence of ultrasonic waves on the decaffeination process of Aceh Gayo arabica coffee. This study employed an experimental method that included 6 treatments (extraction time): K1 (2 minutes), K2 (4 minutes), K3 (6 minutes), K4 (8 minutes), K5 (10 minutes), and K6 (12 minutes). The variables measured in this study included caffeine regain, chlorogenic acid levels, and organoleptic test results. The collected data was analyzed using (SPSS) software version 30. This study found the best results in treatment K4 (8 minutes), which showed caffeine recovery of 56.83%, chlorogenic acid content of 12.3%, and neutral sensory evaluation (4) for color, acidity, and aroma according to panelists.